Design of a microservices architecture in virtual containers - Elizalde Valencia, Samantha Yazmin (2025)
This article presents the methodological proposal for the design and implementation of a containerized microservices architecture. The proposal covers the methodologies used for the research phase of the initial stages of project development, as well as the methodology used to create a test computing system. An architecture based on domain architectures is proposed, as well as the design of the system's physical architecture, based on the requirements presented by the collaborating institution for the test case. The results describe the configuration of the microservices and containers, as well as their integration into a common network of running services.